Respuesta :

Answer:

The answer is C.

Step-by-step explanation:

Just go to Desmos.com and plug it in.

For this case we have:

Let k> 0:

To graph[tex]y = f (x) + k,[/tex] the graph k units is moved up.

To graph [tex]y = f (x) -k[/tex], the graph moves k units down.

Let h> 0:

To graph [tex]y = f (x-h)[/tex], the graph moves h units to the right.

To graph [tex]y = f (x + h),[/tex] the graph moves h units to the left.

So, we have:

[tex]y = f (x) = \sqrt [3] {x}[/tex]

Shifted 1 unit down and 4 to the left means:

[tex]k = 1\\h = 4[/tex]

[tex]y = f (x) = \sqrt [3] {x + 4} -1[/tex]

Answer:

Option D